Tożsamość kulturowa w perspektywie integracji europejskiej - Stawarz, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2008)
The beginning of the 21st century is the time of a new challenge for the Polish nation. Standing onthe threshold of a new century, it has also stood on the ‘threshold’ of the united Europe.Culture is a binder thanks to which it is possible to discover and to maintain peoples’ identityand the bonds connecting individual members of the nation. The multitude of nations is a variety whichmakes Europe not a monolith in relation to culture; instead, it constitutes a mosaic of different culturesand philosophies of life.The Church does not try to identify with any of the culture patterns, but it seeks its place amongthe diversity of their forms. However, one can talk about the development of a Christian culture modelresulting from the faith and the presence of the evangelical message in the whole of the Christians’ life.In the survey concerning Poland’s accession to the European Union, Polish people have expressedtheir hopes and fears connected with the process of integration. As many as 11% of the people surveyedexpressed their anxiety related to the adverse effect upon culture and customs. The Church in its socialinstruction continuously emphasizes the necessity of maintaining one’s own cultural identity byparticular ethnic, national and regional groups. The united Europe is to become not exactly a federationof countries, but rather the home of homes. In the everyday life of the new united Europe the system ofnorms, values and patterns of religious and cultural behaviour are going to be verified. Both the scepticsand the enthusiasts of the integration process are looking for a place and a role for the Polish Christiansin the secularized European society.